2004
DOI: 10.1063/1.1728290
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of light-sensitive resonant-tunneling-diode devices

Abstract: We present a method to include the effects of light excitation on two different models of resonant-tunneling-diode-based devices. Our approach takes into account both photoconductive and charge accumulation effects responsible for shifting the static I -V curve when the structure is under light excitation. Computational simulations led to good agreement between the model and experimental results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
19
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 14 publications
1
19
0
Order By: Relevance
“…15,16,18 As a result, the current-voltage (I(V)-) characteristic under illumination is shifted towards lower bias voltages (see Fig. 1(c)).…”
Section: Photocurrent-voltage Relation Of Resonant Tunneling Diode Phmentioning
confidence: 99%
See 1 more Smart Citation
“…15,16,18 As a result, the current-voltage (I(V)-) characteristic under illumination is shifted towards lower bias voltages (see Fig. 1(c)).…”
Section: Photocurrent-voltage Relation Of Resonant Tunneling Diode Phmentioning
confidence: 99%
“…15 Coelho et al have provided a model of the RTD current-voltage characteristic under illumination by calculating a photoinduced voltage shift and integrating it into Schulman's equation. 16 The voltage shift is given as a function of accumulated holes and is assumed constant across the whole bias voltage range. However, in our study, the photo-induced voltage shift is found to be strongly dependent on the bias voltage.…”
Section: Photocurrent-voltage Relation Of Resonant Tunneling Diode Phmentioning
confidence: 99%
“…[14][15][16][17] In the biased RTD photo-excited electron hole pairs become locally separated by the applied field, which causes a variation of the internal field and hence the transmission properties of the RTD are altered. [18][19][20] Here, we report on an RTD-photosensor with a cavityenhanced efficiency for the telecommunication wavelength range at 1.3 lm operated at room-temperature. The sensor is based on a GaAs/AlGaAs RTD with a quaternary GaInNAs absorption layer integrated in an optical cavity consisting of AlAs/GaAs distributed Bragg reflectors (DBRs).…”
mentioning
confidence: 99%
“…Different structures and geometries have been proposed to optimize the RTD photo detection for different optical wavelengths. [13][14][15] In order to enhance greatly the conversion from an optical signal into an electrical signal, an absorption layer must be incorporated in the RTD structure (Figure 2). …”
Section: Rtd-pd Design and Fabricationmentioning
confidence: 99%